TANGGUNG JAWAB HUKUM ATAS KERUGIAN AKIBAT WANPRESTASI DALAM PERJANJIAN JUAL BELI TANAH (STUDI KASUS DI PENGADILAN NEGERI SIDOARJO) PUTUSAN NOMOR 16/Pdt.G/2019/PN Sda - Putri Lilasari; Abrahan Ferry Rosando (Gapenas Publisher, 2022)
Buying and selling is a form of general transaction that is often carried out by the public. Usually the sale and purchase agreement are made orally or in writing on the basis of the agreement of the parties involved parties (seller and buyer). This study aims to determine the process of implementing land and house sale and purchase agreements, regulations and rights and obligations between the seller and the buyer, and know the legal responsibility if one of the parties commits error. This research method is normative because in this study the researched are legal rules, legal principles and legal responsibility for implementation of the sale and purchase agreement of land and houses in Sukoharjo Regency. The nature of this research is descriptive which describes thoroughly and systematically about sale and purchase agreement. The results of the study show the process of buying and selling land and houses in Sukoharjo Regency, it must meet material, formal, and legal requirements. Condition material, which includes buyers, sellers and land objects, then the formal requirements include: original land certificate, proof of having paid PBB, BPHTB deposit letter, PPh deposit letter, and seller and buyer data which includes: KTP and KK, and the legal requirements of article 1320 Civil Code. After fulfilling the conditions, then both parties must do the following: a written agreement made by the PPAT party which is then signed by the parties. After signing the deed of agreement, the agreement then arises deal. After the agreement and signing of the agreement, the rights arise and obligations for the parties that must be carried out, the right of the seller is to receive payment for land and houses, while the buyer's rights are to receive ownership rights to the land and a house in the form of a certificate. The seller's obligation is to hand over the ownership rights to the land and house in the form of a certificate to the buyer, then the buyer's obligation is to pay price according to agreement. Legal responsibility if one of the parties commits errors due to default, must pay compensation based on article 1243 Civil Code. Meanwhile, if an error is made by one of the parties as a result of against the law committed by him, he must pay compensation based on article 1365 Civil Code